Association of Treatment of Chorioamnionitis with Non-Beta Lactam Antibiotics and Postcesarean Infectious Morbidity - Glover, Angelica V.; Battarbee, Ashley N.; Heine, Robert Phillips; Dotters-Katz, Sarah (American Journal of Perinatology, 2020)
Objective Chorioamnionitis (CAM) is associated with postcesarean (CS) infectious morbidity (IM). Beta-lactam antibiotics (BLA) are used to treat CAM. It is uncertain if women who cannot receive BLA attain similar benefit from treatment of CAM with non-BLA.Study Design Retrospective cohort of women with CAM is delivered by CS in the maternal-fetal medicine units CS registry. We compared IM in women who received BLA versus women who received non-BLA. The primary outcome was a composite of endometritis, wound complication, necrotizing fasciitis, septic pelvic thrombophlebitis, and pelvic abscess. Multivariable logistic regression estimated odds ratios for the association of non-BLA treatment with IM outcomes.Results A total of 3,063 (93%) women received BLA, and 232 (7%) received non-BLA. Groups had similar rates of composite post-CS IM (10.6 vs. 12.1%, p = 0.5). After adjusting for confounders, treatment of CAM with non-BLA was not associated with post-CS IM (adjusted odds ratio [AOR] 1.1, 95% confidence interval [CI] 0.6–1.7), endometritis (AOR 1.1, 95% CI 0.7–1.8), or wound complications (AOR 1.2, 95% CI 0.5–3.2).Conclusion Women with CAM who receive non-BLA and require CS may not be at increased risk of postoperative infections complications, compared to women who receive BLA.
Keywords: antibiotics; cesarean; chorioamnionitis; intraamniotic infection; penicillin; wound infection